PURIFICATION AND PHYSICAL PROPERTIES OF GROUP C STREPTOCOCCAL PHAGE-ASSOCIATED LYSIN - Fischetti, Vincent A. (The Rockefeller University Press, 1971)
A purification procedure for the Group C phage-associated lysin is described utilizing tetrathionate to protect the enzyme's -SH group(s) from thiol-inactivating agents. A 652-fold purification has been accomplished yielding a solution in which the enzyme activity corresponds to essentially a single band on polyacrylamide gel which accounts for 70% of the total protein in the preparation. A molecular weight of 101,000 and frictional ratio of 1.526 was determined for the lysin utilizing experimentally determined values for its Stokes radius and sedimentation coefficient.